Attributions of poverty among social work and non-social work students in Croatia - Družić Ljubotina, Olja; Ljubotina, Damir (2007)
Aim. To investigate perceived causes of poverty in Croatia as seen by students and examine the differences in attributions of poverty between students of social work, economics and agronomics. Methods. The study included 365 participants, students of social work (n=143), economics (n=137) and agronomics (n=82). A new questionnaire called Attribution of poverty scale was used, consisting of 4 factors: 1) individual causes of poverty (lack of skills and capabilities, lack of effort, poor money management, alcohol abuse etc.), 2) micro-environmental causes (poor family, region, single parenthood etc.) 3) structural/societal causes (poor economy, consequences of political transition, war) 4) fatalistic causes (bad luck, fate, God's will). A questionnaire on values measuring 5 dimensions: humanistic values, family values, striving for self-actualization, traditional values and hedonistic values was also used. Items were rated on a 5-point Likert-type scale on both questionnaires. Results. Students of all three fields put most emphasis on structural causes of poverty (M=3.54  0.758), followed by environmental (M=3.18  0.604), then individual (M=2.95  0.681), with fatalistic factors at the back of the list (M=1.81  0.743). It was found that social work students perceive individual factors as significantly less important (ANOVA, F-value=12.55, P<0.001) causes of poverty that students of economics and agronomics. A correlation was found between humanistic values and perceived structural causes of poverty (Pearson correlation, r=0.267, P<0.001), micro-environmental causes of poverty (Pearson correlation, r=0.185, P<0.001) and also between traditional values and structural causes of poverty (Pearson correlation, r=0.168, P<0.001), micro-environmental causes of poverty (Pearson correlation, r=0.170, P<0.001), and fatalistic causes of poverty (Pearson correlation, r=0.149, P<0.001). Conclusion. Students see structural/societal factors (poor economy, political transition) as main causes of poverty in Croatia. Less importance is given to individual factors connected with individual's personal characteristics, while luck and fate are seen as least important. Students of social work see individual causes as less important than students of agronomics and economics. Students with strong humanistic and traditional values put more emphasis on external sources of poverty.
Projekt MZOS
Projekt MZOS
ENG